2022
DOI: 10.1002/smll.202201123
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanobubble Mechanical Stress Induces the Piezo1‐Ca2+‐BMP2/Smad Pathway to Modulate Neural Stem Cell Fate and MRI/Ultrasound Dual Imaging Surveillance for Ischemic Stroke

Abstract: Neural stem cells (NSCs) are used to treat various nervous system diseases because of their self‐renewal ability and multidirectional differentiation potential. However, an insufficient ability to track their migration in vivo and poor control over their survival and differentiation efficiency are two major critical challenges for clinical application. Here, it is shown that when magnetic nanobubbles (MNBs), which are assembled from magnetic nanoparticles, are internalized by NSCs, intramembrane volumetric osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…11,12 Magnetic nanocomposites and magnetic stimuli have been used to accelerate bone repair, treat nervous system diseases, trace drug delivery in real time and achieve magnetic hyperthermia. 13–16 Additionally, our previous works have revealed that a potential mechanism for magneto-promoted osteogenesis is magnetically actuated mechanical stimuli delivered by nano-deformation of magnetic composites to cells, while our simulations demonstrate that the grafting modification of nanoparticles (NPs) can significantly affect the dynamics of the polymer matrix. 17,18 However, preparing magnetic nanocomposites for bone defect regeneration faces an important challenge, i.e.…”
Section: Introductionmentioning
confidence: 72%
“…11,12 Magnetic nanocomposites and magnetic stimuli have been used to accelerate bone repair, treat nervous system diseases, trace drug delivery in real time and achieve magnetic hyperthermia. 13–16 Additionally, our previous works have revealed that a potential mechanism for magneto-promoted osteogenesis is magnetically actuated mechanical stimuli delivered by nano-deformation of magnetic composites to cells, while our simulations demonstrate that the grafting modification of nanoparticles (NPs) can significantly affect the dynamics of the polymer matrix. 17,18 However, preparing magnetic nanocomposites for bone defect regeneration faces an important challenge, i.e.…”
Section: Introductionmentioning
confidence: 72%
“…Nanomaterial-assisted NSC therapy has led to significant progress in the treatment for ischemic stroke disease. A recent finding reported by Li et al [ 59 ] showed that a type of magnetic nanobubbles (MNBs) fabricated through the self-assembly of poly-glucose sorbitol carboxymethyl ether-modified (γ-Fe 2 O 3 )-SPIONPs can guide NSC differentiation fate by activation of the bone morphogenetic protein 2 (BMP2)/Smad biochemical signaling pathway. BMP signaling plays a pivotal role in brain development and NSC behavior, and it has been associated with a large number of related biological processes such as cell growth and cell differentiation[ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that the multifunctional nanomaterials that target lncRNA have a significant amount of promise to improve stem cell-based therapeutics for the treatment of strokes. It has been demonstrated that when neural stem cells internalize magnetic nanobubbles (MNBs), which are assembled from magnetic nanomaterials, intramembrane volumetric oscillation of the MNBs causes an enhancement in intracellular hydrostatic pressure and cytoskeleton force, which ultimately leads to the activation of the Piezo1-Ca 2+ mechanosensory channel [ 131 ]. This, in turn, activates the BMP2/Smad biochemical signalling pathway, which ultimately results in the differentiation of neural stem cells into neurons.…”
Section: Nanoneurosciencementioning
confidence: 99%